Family Influences on Caries in Grenada - Danielle Mitnick; Ashley Dills; Amy M. Smith Slep; Richard E. Heyman; Jill Giresi (MDPI AG, 2020)
If high-conflict family environments are cariogenic across cultures, and can be studied in cultures where both these environments and cariogenic dental practices are particularly prevalent, this would afford the opportunity to examine how these two pathways of risk might interact, laying the stage for culturally competent, integrated prevention efforts. The first investigation involved qualitative data about perceptions of oral health and family stressors in Grenadian families with school-aged children. The second study used a questionnaire and observational data to assess relations among oral health behaviors, relationship satisfaction, parenting, and child behavior; it also included a pilot study of Motivational Interviewing. Most of the themes discussed in focus groups suggested overlap between U.S. and Grenadian parents; possible culture-specific issues were high prevalence of single-parent homes, normativity of physical discipline, less preventive dental care, and more fatalistic view of oral health outcomes. Significant associations were found between parent and child oral health behaviors, between child externalizing and internalizing behaviors, and between family variables (e.g., relationship satisfaction, child behavior) and oral health behaviors (e.g., parent flossing, child brush time). The results strongly support the need for research on the relations between family functioning and oral health to be embedded within culture.